Ensuring the Quality of Pharmacy Training Program: A Foundation for Developing High-Quality Healthcare Workforce and Achieving Sustanable Development Goals - Tran Thi Thu Trang; Nguyen Thi Song Ha; Phan Thi Thanh Thao; Nguyen Thuy Van (PT. Riset Press International, 2026)
In the context of Vietnam's efforts to achieve the Sustainable Development Goals (SDGs), improving the quality of the healthcare workforce, particularly in the pharmacy sector, plays a foundational role. This article analyzes the role of educational accreditation as a strategic tool for training a generation of pharmacists who meet the demands of sustainable development. Using a literature review method and analyzing policy documents, the paper clarifies the multidimensional relationship between accreditation of pharmacy training programs and the implementation of these goals, particularly Sustainable Development Goal 3 (Ensure healthy lives and promote well-being for all at all ages). The study indicates that, despite encouraging results (with 22 accredited pharmacy training programs by September 2024), the biggest challenge remains the shift from a “compliance” mindset to the creation of a true “quality culture” in training institutions, along with challenges related to resource limitations and the applicability of accreditation standards. Based on this, the paper proposes coordinated solutions involving government authorities, educational institutions, and society to improve the effectiveness of accreditation efforts, contributing to national healthcare security and promoting sustainable development.